Herbal-based compounds: A review on treatments of cryptosporidiosis - Fatemeh Namazi; Seyed Mostafa Razavi (International Journal for Parasitology: Drugs and Drug Resistance, 2024)
Cryptosporidium, a monoxenous apicomplexan coccidia, is a prevalent diarrhetic and an opportunistic agent, mainly in immunocompromised individuals. As there are few chemotherapeutic compounds that have limited efficacy, we need to identify new compounds or specific parasite targets for designing more potent drugs to treat cryptosporidiosis. Herbal products with low toxicity, environmental compatibility, wide therapeutic potential, and abundant resources can be considered alternatives for treatment. The current review tried to summarize the studies on plants or herbal bioactive constituents with anti-cryptosporidial activities. Based on constituents, plants act via different mechanisms, and further investigations are needed to clarify the exact mechanisms by which they act on the developmental stages of the parasite or host-parasite relationships.